Investigations of Necropoleis of Kytaion in 2014–2018 - Khrshanovskiy, Vladimir (Hyperboreus, 2019)
A survey of the excavations on necropoleis of Kytaion conducted by the archaeological expedition of the Institute of Archaeology, RAS  in 2014–2018.